The Effect of Regional Financial Ratios on the Regional Financial Performance of Regency/City Governments in East Java Province During the COVID-19 Pandemic and After COVID-19 - Dwi Santoso; Harlina Meidiaswati (Publikasi Indonesia, 2025)
This study aims to analyze the effects of the Regional Financial Independence Ratio, Local Revenue Effectiveness Ratio (PAD), Regional Expenditure Efficiency Ratio, Regional Expenditure Management Ratio, Local Revenue Growth Ratio, and Fiscal Decentralization Degree Ratio on the financial performance of local governments. It also investigates the differences in financial performance before and after the COVID-19 pandemic in regencies and cities across East Java Province. Multiple linear regression analysis and the paired samples test are used in this quantitative study. The study uses secondary data from the regional budget realization reports (APBD), sourced from the official website of the Directorate General of Fiscal Balance (DJPK), Ministry of Finance of the Republic of Indonesia. The sample includes 38 regencies/cities over the 2020–2023 period, with a total of 152 observations. The results indicate that partially, only the Local Revenue Growth Ratio has a significant effect on financial performance, while simultaneously, all financial ratios show significant influence. These outcomes are interpreted through the mathematical logic of each ratio and supported by previous research. Furthermore, the paired sample test reveals significant differences in financial performance between the pandemic and post-pandemic periods, suggesting a decline after the pandemic. The findings underscore the crucial role of local revenue growth in enhancing financial performance and highlight the importance of adaptive fiscal recovery strategies in the post-pandemic era. This study is expected to serve as an evaluative reference for local governments in formulating more effective and sustainable financial management policies.